Elevation Drives Gradients in Surface Soil Temperature Within Salt Marshes. Issue 10 (27th May 2019) - Alber, Merryl; O'Connell, Jessica L.
Abstract: Elevation differences in salt marshes result in numerous ecological consequences as a result of variation in tidal flooding. We demonstrate here that elevation differences are also negatively correlated with soil temperature on the marsh platform, irrespective of tidal flooding. Field observations of soil temperature at 10‐cm depth in a Georgia marsh showed that elevation increases of 0.5 m corresponded to decreases in average soil temperature of 0.9–1.7°C during both winter and summer. Landsat 8 estimates of land surface temperatures across the marsh in dry (nonflooded) scenes also showed that temperature decreased with increasing elevation, which was consistent with soil observations. Similar satellite results were also found in a test marsh in Virginia. Biological reactions are temperature‐dependent, and these findings indicate that metabolic processes will vary over short distances. This is important for accurately estimating marsh metabolism and predicting how changes in temperature will affect future productivity. Key Points: Surface soil temperature exhibits spatial variability within salt marshes and is inversely correlated with elevation on the marsh platform Satellite estimates of surface temperature exhibit these same relationships at broader scales We know little about how small‐scale variability in soil temperature affects rates of salt marsh processes